Malaysian stock index futures market hedging effectiveness: symmetric and asymmetric model - Haron, Razali; Ayojimi, Salami Monsurat (IIUM Institute of Islamic Banking and Finance, 2019)
With consistent repetition in the volatility of the market locally and globally, portfolio managers are seriously concern on the destruction of their portfolio value. Hence, this study examines the hedging effectiveness of the Malaysian derivatives market using a dynamic modelling approach – GARCH and TGARCH models. Daily closing prices of KLCI, KLCI-F and basis are used for the period from June 1, 2009 to August 16, 2016. The study quantifies optimal hedge ratios prior to quantify effectiveness of the hedging mechanism in Malaysia. This study concludes that an asymmetric hedging model is more effective than a symmetric hedging model. This result supports that hedging is dynamic and effective in the Malaysian derivative market.